2019
DOI: 10.3389/fpsyg.2019.01986
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Career Choices: Paths Toward Studying a Degree in Physical Activity and Sport Science

Abstract: Drawing on Social Cognitive Career Theory (SCCT), we examined factors affecting interest in pursuing a degree in Physical Activity and Sport Science (PASS) among Spanish teenage students. Although women were awarded 55.1% of all bachelor degrees in Spain in 2017–2018, female enrollment in PASS degrees is decreasing and currently stands below 20% across the country. To better understand the under-representation of women in this field, 4146 students (50.2% girls; mean age = 16.82 years; SD = 0.837) participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 44 publications
5
15
0
4
Order By: Relevance
“…Prior research has shown that gender plays an important role in career orientation and role models affect the idea of one's professional role with respect to gender. A self-concept that does not critically evaluate these patterns will restrict adolescents' career orientation and thus inhibit chances for development [58,59]. Young women often are more family-minded and state career and family goals as equally important [55].…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that gender plays an important role in career orientation and role models affect the idea of one's professional role with respect to gender. A self-concept that does not critically evaluate these patterns will restrict adolescents' career orientation and thus inhibit chances for development [58,59]. Young women often are more family-minded and state career and family goals as equally important [55].…”
Section: Discussionmentioning
confidence: 99%
“…A raíz de lo anterior, se han identificado trabajos sobre las brechas de género en carreras de Ciencias de la Actividad Física y el Deporte (CAFD), Cultura Física y otras similares a PEF. En España, Serra et al (2019a) publicaron datos sobre la presencia de mujeres en los estudios de CAFD en los dos campus del Instituto Nacional de Educación Física de Cataluña-INEFC (Lleida y Barcelona); reportan que en el curso 1999/2000 el 35 % de la matrícula total era femenina, valor que muestra un descenso notable hasta el curso 2014/2015, donde se registró un 17,3 %. La investigación también revela que, entre las especialidades de Magisterio en Cataluña, la de Educación Física es la que posee una menor presencia femenina entre los cursos de los años 2000/2001 y 2011/2012, nunca superó el 50 % de la matrícula total anual.…”
Section: Estado De La Cuestión Y Perspectivas Teóricasunclassified
“…Eleven ESAs (eight men and three women) volunteered to participate in the study and met the selection criteria. The greater presence of men in the sample reflects the distribution of male and female students in the PASS degree in Spain (just 18% of students enrolled in this degree are female) (Serra et al, 2019). At the time of data collection, the ESAs (listed with their pseudonyms in Table 1) were aged between 19 and 24 years (M age = 20.7, SD = 1.6).…”
Section: Participantsmentioning
confidence: 99%